Identification of Salt Tolerance-related microRNAs and Their Targets in Maize (Zea mays L.) Using High-throughput Sequencing and Degradome Analysis - Fu, Rong; Zhang, Mi; Zhao, Yinchuan; He, Xuechuan; Ding, Chenyun; Wang, Shuangkuai; Feng, Yan; Song, Xianliang; Li, Ping; Wang, Baohua (Frontiers in Plant Science, 2017)
To identify the known and novel microRNAs (miRNAs) and their targets that are involved in the response and adaptation of maize (Zea mays) to salt stress, miRNAs and their targets were identified by a combined analysis of the deep sequencing of small RNAs (sRNA) and degradome libraries. The identities were confirmed by a quantitative expression analysis with over 100 million raw reads of sRNA and degradome sequences. A total of 1040 previously known miRNAs were identified from four maize libraries, with 762 and 726 miRNAs derived from leaves and roots, respectively, and 448 miRNAs that were common between the leaves and roots. A total of 37 potential new miRNAs were selected based on the same criteria in response to salt stress. In addition to known miR167 and miR164 species, novel putative miR167 and miR164 species were also identified. Deep sequencing of miRNAs and the degradome (with quantitative reverse transcription polymerase chain reaction (qRT-PCR) analyses of their targets) showed that more than one species of novel miRNA may play key roles in the response to salinity in maize. Furthermore, the interaction between miRNAs and their targets may play various roles in different parts of maize in response to salinity.